An epidemiological study of low back pain in a tertiary care hospital of Jammu, Jammu and Kashmir, India - Gupta, Rishabh; Mahajan, Shavi; Dewan, Deepika; Gupta, Rajat (International Journal of Research in Medical Sciences, 2017)
Background: Backache is a national, personal and clinical problem. It is experienced by most of the population at some time and is a drain on the nation’s resources. Personally, it is distressing because it can remain a major unresolved dilemma and clinically it poses challenges in diagnosis and treatment. Methods: The present cross sectional study was conducted among 200 patients presenting with chronic low back pain, in the OPD of Post Graduate Department of Orthopaedics, Govt. Medical College, Jammu over a period of one year from November 2006 to October 2007. Results: The average age of patients was 38.39 years with slight male predominance. Majority of the patients were non-sedentary workers. In majority of the cases (58%), duration of low backache was from 3 months to 1 year with the average of 25.8 months (2.158 years). The commonest mode of presentation was low back pain with radiation to lower limbs. Seasonal variation in the intensity of pain was observed in 50% of the cases. Tenderness of the spine was the commonest physical sign. Disc degenerative disease was found to be commonest cause of low backache, being present in 72% of the cases. Conclusions: Low back pain is common in 3rd and 4th decade of life. The commonest mode of presentation was low back pain with radiation to lower limbs. Disc degenerative disease was found to be commonest cause of low backache, being present in 72% of the cases.